Stimulatory role of interleukin 10 in CD8 T cells through STATs in gastric cancer - Jianjun Xi; Mingzheng Xu; Zongchang Song; Hongqiang Li; Shumin Xu; Chunmei Wang; Haihan Song; Jianwen Bai (Tumor Biology)
CD8 + T cells are considered to be critical in tumor surveillance and elimination. Increased CD8 + T cell frequency and function is associated with better prognosis in cancer patients. Interleukin 10 is a cytokine with controversial roles in CD8 + T cell–mediated anti-tumor immunity. We therefore examined the interleukin 10 expression and consumption in CD8 + T cells harvested from the peripheral blood and resected tumors of gastric cancer patients of stages II–IV. We found that the gastric cancer patients presented significantly elevated frequencies of interleukin 10–expressing cells in both CD4 + and CD8 + T cells compared to healthy controls. But distinctive from the interleukin 10–expressing CD4 + T cells, which increased in frequency in advanced cancer, the interleukin 10–expressing CD8 + T cells did not increase with cancer stage in the peripheral blood and actually decreased with cancer stage in resected tumor. Interleukin 10 and interleukin 10 receptor expression was also enriched in interferon gamma–expressing activated CD8 + T cells. Compared to interleukin 10–nonexpressing CD8 + T cells, interleukin 10 receptor–expressing CD8 + T cells secreted significantly elevated interferon gamma levels. Treatment of anti-CD3/CD28-stimulated, purified CD8 + T cells with interleukin 10 alone could significantly enhance CD8 + T cell survival, an effect dependent on interleukin 10 receptor expression. Interleukin 10 also increased CD8 + T cell proliferation synergistically with interferon gamma but not alone. Analysis of downstream signal transducer and activator of transcription molecules showed that interleukin 10 treatment significantly increased the phosphorylation of signal transducer and activator of transcription 3 and signal transducer and activator of transcription 1 to lesser extent. Together, these results demonstrate that interleukin 10 possessed stimulatory roles in activated CD8 + T cells from gastric cancer patients.